Education for all global promises, national challenges - Baker, David, 1952 Jan. 5-; Wiseman, Alexander W., 1968- (International perspectives on education and society ;, 2007)
Since the World Conference on Education for All (EFA) in Jomtien, Thailand in 1990, the push for modern mass schooling has become a primary focus of national education policymakers and researchers around the world. The EFA declaration that grew out of this conference served as a culmination of a century-long movement to transform existing national educational systems into the most comprehensive mass system of schooling ever devised. Comparative education researchers have been studying both the promises and the challenges surrounding EFA for decades, but in comparative education research literature there is still neither consensus on the impact that EFA has nor clearly identified global trends in either EFA policymaking or policy implementation. It seems that for every promise that EFA brings, there is an accompanying challenge.It is this struggle between the global promises and the national challenges that this volume of "International Perspectives on Education and Society" seeks to identify and explain. Chapters range from critical syntheses of EFA policymaking or policy implementation to original comparative education research on the impact that EFA has had in specific nations or across clusters of nations. It compares and contrasts the promises of EFA v. implementation of policy. The international contributions ensure global coverage of content. It is part of the "International Perspectives on Education and Society" series.